Synergistic effects of electric current and GAs/Bi₂O₃/ZIF-67 photocatalysis on graphite in a planar microreactor applied for tetracycline degradation and kinetic pathway analysis - Negin Entezami; Mehrdad Farhadian; Ali Reza Solaimany Nazar (Scientific Reports)
Abstract The presence of antibiotic pollutants such as tetracycline (TC) in water bodies poses a major environmental and health concern due to their persistence and resistance to conventional treatment. To address this issue, a novel GAs/Bi2O3/ZIF-67 composite was synthesized and coated onto graphite plates using a spin-coating method. This composite was integrated into a planar microreactor system comprising conductive FTO glass and a PDMS spacer, designed to enhance photocatalytic performance through simultaneous application of a low-voltage electric current. The composite was characterized using XRD, UV-Vis-DRS, FTIR, PL, SEM, EDX, TEM, EIS, and Photocurrent techniques. Photocatalytic activity was evaluated under various operational parameters. Under optimized conditions (pH = 4, the concentration of TC/load of photocatalyst = 0.2 (mg.m2/g.L), and retention time = 360 s), applying 1.8 V increased degradation efficiency from 88 to 99% and reduced treatment time by 33%. A synergistic index of 1.66 confirmed the positive interaction between photocatalysis and electric current. Kinetic studies indicated that the reaction rate was the limiting factor. The system maintained an efficiency of over 80% for 780 min, exhibiting stable performance under flow reversal. These results demonstrate the system’s potential as a fast, scalable, and energy-efficient approach for treating industrial pharmaceutical wastewater.